An Assessment of beach management units in combating illegal fishing in lake Victoria, Tanzania: A case of Bukoba district - Kashililika, Edwin W. (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfilment of the Requirements for the Degree of Master of Science in Environmental Management (MSc EM) of the Mzumbe University